2018
DOI: 10.1111/pan.13325
|View full text |Cite
|
Sign up to set email alerts
|

Erector spinae plane block for inguinal hernia repair in preterm infants

Abstract: Neuro-axial anesthesia has been the preferred technique for inguinal hernia repair when attempting to avoid general anesthesia in neonates and preterm infants. We present a case where an erector spinae plane block was used successfully for this surgery. Hemodynamic stability, minimal anesthetic requirements, and excellent pain control were documented. This block promises to be a valuable and safe alternative for inguinal hernia repair, accompanying the path of neuroprotective anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 5 publications
1
20
0
4
Order By: Relevance
“…After reviewing the literature regarding ESPBs in children, we found 33 publications as of May 2019 (see Table ) . These included 28 different case reports (three or less patients), three case series (greater than three patients), and two randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the literature regarding ESPBs in children, we found 33 publications as of May 2019 (see Table ) . These included 28 different case reports (three or less patients), three case series (greater than three patients), and two randomized controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the ESP block is limited to the thoracic region in the pediatric population, with only a few reports (Table 1). It has been reported to provide effective postoperative analgesia for thoracic surgeries [610], nephrectomy [11], inguinal hernia repair [12], and laparoscopic cholecystectomy operations [13] in children. To our knowledge, ESP block performed in the lumbar region has not been reported in children.…”
Section: Discussionmentioning
confidence: 99%
“…In some previous reports, relatively smaller volumes of local anesthetic or similar volumes and concentrations as reported in this case were used. Hernandez et al [12] used a volume of 0.2 ml/kg of 0.25% bupivacaine to perform an ESP block for inguinal hernia repair in a 2-month-old male patient. They also reported that they were able to achieve adequate anesthetic spread and analgesia with a volume of 0.2–0.3 ml/kg in other pediatric patients undergoing thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…El bloqueo del ESP es una técnica recientemente descrita en pacientes adultos y para manejo de dolor neuropático, según mencionado por los autores (5). Actualmente el bloqueo ESP se viene realizando en la población pediátrica, con solo pocos informes (Tabla I), para manejo del dolor postoperatorio de cirugías torácicas (11)(12)(13)(14)(15)(16)(17), nefrectomía (18), reparación de hernia inguinal (19), colecistectomía laparoscópica (20), displasia de cadera (21) e hipospadias (22). Hasta donde sabemos, el bloqueo ESP para dolor neuropático en niños aún no se ha reportado.…”
Section: Discussionunclassified